TOTALITARIANISM AS SOCIO-CULTURAL PHENOMENON: PROBLEM OF UNDERSTANDING AND NEW CHALLENGES IN INFORMATION EPOCH - Авксентьєва, Т.Г.; Чорна, Н.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The theoretic-methodological problems of understanding of totalitarianism as socio-cultural phenomenon are considered in the article. The special attention is paid to differentiation of categories „totality” and „totalitarian” in socio-cultural field of West European and not western types of societies. Not only the practical forms of the totalitarian regimes are analyzed but also their possible modern mutations, totalitarian tendencies, connected to becoming of informative civilization.